Perancangan Sistem Keamanan Pintu Masuk dan Keluar Kendaraan di Perumahan Golden Simalingkar B Medan - Reinhard Simbolon (JURIKOM (Jurnal Riset Komputer), 2019)
Technology makes everything we do easier. The human need for intelligent equipment that can work automatically is increasing, so these automatic equipment are gradually replacing manual equipment. In this paper, we developed an automatic open / close door opening device based on AT89S51 Microcontroller. AT89S51 microcontroller is used as the brain of the performance of this tool. All instructions from the way the tool will be processed in the AT89S51 Microcontroller. The purpose of using this microcontroller is to create an automatic open / close door application system. The process that is done begins with the detection of motion by an infrared sensor. When the sensor detects a movement that passes through the sensor, the LED lights on and the alarm will sound a few seconds, after that a scan of the bar code to the RFId Reader then the doorstop opens automatically.